Restructuración del espacio público en el centro de la ciudad de Cali (2021)
The informal economy in Colombia shows the inability to generate employment in the country taking into account the little guarantee offered for the sector. Within this informal economy we focus on the city of Cali, specifically in commune 3 (Central zone of the city) where this problem is evidenced in greater content. A good development of strategic plan to promote informality at the commercial and public space level benefits the community in general, thus generating greater economic activity, greater demand in employment and certain spaces are recovered at a functional level. For this they were made respective studies to a specific sector of commune 3 and a proposal was made architecture at the level of public space according to the results obtained.